2009
DOI: 10.1042/bst0370873
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic tail of IL-13Rα2 regulates IL-4 signal transduction

Abstract: IL (interleukin)-4 and IL-13 are key cytokines in the pathogenesis of allergic inflammatory disease. IL-4 and IL-13 share many functional properties as a result of their utilization of a common receptor complex comprising IL-13Ralpha1 (IL-13 receptor alpha-chain 1) and IL-4Ralpha. The second IL-13R (IL-13 receptor) has been identified, namely IL-13Ralpha2. This has been thought to be a decoy receptor due to its short cytoplasmic tail and its high binding affinity for IL-13 but not IL-4. IL-13Ralpha2 exists on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…This points to a key role for the cytoplasmic tail of IL-13Ra2 in modulating IL-4 response. Furthermore, as previously described, 20,21 an IL-13Ra2 neutralising antibody restored STAT6 signaling in BEAS2B-FL cells treated with IL-4. As our SPR data demonstrates, this is not due to the antibody preventing IL-13Ra2 binding IL-4, but likely a result of additional extracellular steric hindrance preventing assembly of the IL-4Ra-IL13Ra2 receptor complex, and the resulting association of their cytoplasmic domains.…”
Section: P374amentioning
confidence: 99%
See 1 more Smart Citation
“…This points to a key role for the cytoplasmic tail of IL-13Ra2 in modulating IL-4 response. Furthermore, as previously described, 20,21 an IL-13Ra2 neutralising antibody restored STAT6 signaling in BEAS2B-FL cells treated with IL-4. As our SPR data demonstrates, this is not due to the antibody preventing IL-13Ra2 binding IL-4, but likely a result of additional extracellular steric hindrance preventing assembly of the IL-4Ra-IL13Ra2 receptor complex, and the resulting association of their cytoplasmic domains.…”
Section: P374amentioning
confidence: 99%
“…20,21 This may be a result of the antibody causing steric hindrance around IL-13Ra2, blocking its interaction with IL-4Ra, but it remains unclear whether IL-13Ra2 exerts its regulatory effect on the binding of IL-4 to IL-4Ra via interaction of the extracellular domains of the two receptors, or via the interaction of the cytoplasmic domains of IL-4Ra and IL-13a2.…”
Section: Introductionmentioning
confidence: 99%
“…IL-13 also binds to the other IL-13 receptor subtype a2 (IL-13Ra2) with an even higher affinity. This receptor has been thought to be a decoy receptor due to its short cytoplasmic tail, but it has been shown that IL-13Ra2 may have some signalling capabilities, regulating IL-13 signalling pathways (Tabata and Khurana Hershey, 2007;Andrews et al, 2009). In the canonical pathway triggered by IL-4 and IL-13, binding of either IL-4 to IL-4Ra in IL-4R Type 1 or 2, or IL-13 to IL-13Ra1 in IL-13 receptors results in an activation of janus tyrosine kinase 1 (JAK1), which leads to phosphorylation of tyrosine residues of IL-4Ra, which subsequently liaisons with the transcription factor signal transducers and activators of transcription 6 (STAT6).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, IL-4 induces the production of an IL-1R antagonist considered to be an anti-inflammatory cytokine that blocks IL-1 effects in neutrophils and the recruitment of inflammatory cells by increasing the expression of vascular cell adhesion molecule-1 on the endothelial surface (Ratthé et al 2009). Although the effect of IL-13 binding to IL-13Rα2 is unclear, IL-13 plays a central role in host defense against parasite infection and in the pathogenesis of allergic diseases by binding to IL-4Rα and IL-13α1 (Andrews et al 2009). Thus, the results of this study showing the expression of IL-4R and IL-13R indicate that several immune responses, such as the above-mentioned activity, might occur during the newborn to 2-month-old period, especially in the dome region in which immune responses are pronounced.…”
Section: Discussionmentioning
confidence: 98%